Effect of thermal treatment on physical properties and stability of whipping and whipped cream. (October 2015) - Nguyen, Viet; Duong, Cua T.M.; Vu, Vi
Highlights: Fast cooling promoted partial coalescence in whipping cream. Tempering at 30 °C created convenient condition for forming partial coalescence. Tempering at 20 °C is an suitable choice to stabilize structure of whipped cream. Abstract: The effect of tempering (20, 30 and 40 °C) and the cooling rate (0.5 and 2 °C/min) on physical properties and stability of whipping and whipped cream was investigated. Rheological behavior and light microscope observations showed that tempering at 30 °C and fast cooling created convenient condition for forming partial coalescence between fat globules in whipping cream. This special linkage helped to prevent serum leaking out of whipped cream when storing them at low temperature (4 °C). However, tempering at 20 °C would have been a more appropriate choice to stabilize structure of products through balance different types of partial coalescence in whipped cream during storage.